Deslocamentos, confluências e matizes do conhecimento psicológico na pesquisa sobre educação infantil no Brasil (1999-2020) - Lemos, Adriane Guimarães de Siqueira (2023)
This research is part of the Foundations of Educational Processes line and aims to investigate conceptions of psychology that underlie the academic production on early childhood education. This is a survey of the state of knowledge, considering theories and conceptions that inform the understanding of the child from 0 to 6 years and its constitutive/formative processes in articles, dissertations and theses published between 1999 and 2020. From a critical perspective, the theoretical bases that support the conceptions announced in this production are analyzed, in whose treatment and analysis a multiplicity of references was verified, with the reduction of psychological contributions and the approximation of sociological contributions for the explanation of the child's constitutive processes. The delineation of these foundations reveals the thesis that the foundations of psychology in the production that investigates early childhood education have developed, historically, in a fractured way. Different strands, various explanations, concepts and conceptions were amalgamated, constituting the form-content that has guided research on early childhood education, that is, the fractured explanation of the child's constitutive processes. And this occurs in the wake of society's objective demands, not infrequently disregarding the original and sustaining foundations of the concepts and contributions of psychology. The displacement of this scientific production towards the sociology of the foundations does not change this condition. Rather, it is an expression of the fracture, since the redefinition of the place of children and childhood in the central proposal of the main sociological strand that guides the production analyzed, the Sociology of Childhood, does not do without contributions from psychology. Foundations or rudiments of psychology are, thus, subsumed in the sociological foundations, due to structuring and functional requirements that demand research answers dynamically compatible with the current structural conditions. This is a fractured psychology that reposes the child-society tension. The social fracture composes the relation psychology-education in the production that investigates early childhood education, engendering answers for the explanation of the child in its constitutive processes and formative proposals also fractured. It is also of the social-historical context the demand for fractured and non-totalizing explanatory systems.